The Physico-chemical, morphological, Organoleptic and microscopic study of fresh Arbutus unedo L. fruits from Morocco: Physico-chemical, morphological, Organoleptic and microscopic study of fresh Arbutus unedo L. fruits from Morocco - ELMEJHED, Badreddine (European Journal of Applied Sciences, 2022)
The Arbutus unedo L or Arbutus tree is a leafy tree that represents a large part in the Moroccan ecological ecosystem. However, the poor studies on the fruits of Arbutus unedo in the Mediterranean countries cause poor exploitation and lack in the market. In this sense, the objective of this work focuses on a general description of the fruits of the province of Beni Mellal, such as morphological, organoleptic, microscopic, physico-chemical characteristics (pH, titratable acidity, moisture content, and ash content), lipid, protein and sugar content. For morphological characterization the studied fruit samples were red and red-orange color; With soft consistency and a rough skin; Mean total mass of 4.99 g ±1.38, a mean length of 1.99 cm ±0.28 and a width of 1.89 cm ±0.21. On the basis of physico-chemical analysis, we obtained a moisture content of up to 63.33%±3.21, an acid pH of 3.86±0.01, a titratable acidity of 0.6%±0.06 and an ash content of 0.35%±0.07. In addition, a spectral analysis using ATR-FTIR spectroscopy shows the identification of wave numbers in the (3010cm-1; 2920cm-1) for lipids, a (1600cm-1; 1652cm-1) for proteins and (1035cm-1; 1011cm-1) for sugar. While according to the organoleptic parameters, we found that the fruit was moderately acceptable by the consumers. Comparing with several results, the variation of morphological and physicochemical parameters may be due to different geographical, climatic and tree age parameters. In addition, these results clearly show the need to seek ways of conservation and industrial exploitation.